2019
DOI: 10.1038/s41415-019-0615-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning in dentistry: challenges and opportunities

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…This important finding has been discussed in the literature and could have serious implications for dental education [ 8 ]; hence, dental students and professionals need additional training and education to search for evidence-based information effectively. In a recent study, Khatoon et al demonstrated that dental students might not be competent in the skills and experience required to scrutinise the information shared online [ 28 ]. With the current dramatic move to online education and the imminent surge in the adoption of digital technologies to disseminate educational contents due to the COVID-19 pandemic, such crucial training has become a necessity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This important finding has been discussed in the literature and could have serious implications for dental education [ 8 ]; hence, dental students and professionals need additional training and education to search for evidence-based information effectively. In a recent study, Khatoon et al demonstrated that dental students might not be competent in the skills and experience required to scrutinise the information shared online [ 28 ]. With the current dramatic move to online education and the imminent surge in the adoption of digital technologies to disseminate educational contents due to the COVID-19 pandemic, such crucial training has become a necessity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, how little do we know about their ability to discern and recognize between evidence-based information and unsupported materials? Academic institutions should be aware of this imminent challenge and prepare the teachers and clinical instructors to provide proper guidance to their students about using mobile technology and searching for online information (25).…”
Section: E-learning In Dentistry: a Panoramic Viewmentioning
confidence: 99%
“…Some educators even ban using mobile devices during the lessons as they consider that they can serve as the way of deceiving a teacher during the test or as a factor of distracting attention from educational material. High cost of professional network resources and Learning Management Systems (LMS) does not contribute to the mass introduction of advanced educational technologies as well [1,5,17].…”
Section: Introductionmentioning
confidence: 99%